Pendampingan Penerapan Aplikasi Pembelajaran Bahasa Inggris Berbasis IT Bagi Guru Bahasa Inggris di MTs. Negeri 2 Lamongan - Nirwanto Maruf; Dahlia Husain; Nuri Rahmiati (Jurnal SOLMA, 2021)
Background: Distance learning has been a major source of learning since the covid-19 pandemic hit the world. Unfortunately, more research shows that distance learning faces many obstacles, so learning goals are not achieved. This community service aims to assist English teachers in implementing IT-based English learning applications, namely Chatbot and Smart Rector. The teachers chosen as partners are teachers of Lamongan State MTs 2. Method: The implementation of this devotion follows the steps, that is; conduct preliminary research, conduct needs analysis, hold seminars, hold workshops, and then conduct monitoring and evaluation. Results: Teachers understand and master the concept and application of e-learning methods by using mobile devices such as smart phones, tablets, and laptops. Conclusion: The knowledge of English teachers at MTS Negeri 2 Lamongan has significantly improved in terms of application knowledge and e-learning methods using mobile devices.